2016
DOI: 10.3389/fpsyg.2016.01437
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Activity of Ventromedial Prefrontal Cortex by Anodal tDCS Enhances the Trustee’s Repayment through Altruism

Abstract: Trust and trustworthiness are essential to an efficient economy and play crucial roles in social life. Previous evidence from behavioral experiments has revealed that the trustworthiness of individuals is closely related with their altruistic preference. It has been demonstrated that the ventromedial prefrontal cortex (vmPFC) is associated with decisions involving trustworthiness. Moreover, vmPFC lesion patients showed less trustworthiness and altruism than control subjects, indicating the indispensable role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…This montage was chosen to deliver current to the mPFC (modeled with tDCS explore neurotargeting software by Soterix Medical, Kempe, Huang, & Parra, 2014; Figure 1) while avoiding cathodal stimulation over the prefrontal cortex. This tDCS montage is comparable to previously used montages that aimed to stimulate the vmPFC and simultaneously avoid prefrontal stimulation with the opposing electrode (Abend et al., 2016; Civai, Miniussi, & Rumiati, 2015; Zheng et al., 2016). Intensity of 2 mA was chosen to “correct” for stimulation intensity loss when electrodes are placed further away from one another (Moliadze, Antal, & Paulus, 2010), which was done to potentially reach deeper neural structures (Dmochowski, Datta, Bikson, Su, & Parra, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This montage was chosen to deliver current to the mPFC (modeled with tDCS explore neurotargeting software by Soterix Medical, Kempe, Huang, & Parra, 2014; Figure 1) while avoiding cathodal stimulation over the prefrontal cortex. This tDCS montage is comparable to previously used montages that aimed to stimulate the vmPFC and simultaneously avoid prefrontal stimulation with the opposing electrode (Abend et al., 2016; Civai, Miniussi, & Rumiati, 2015; Zheng et al., 2016). Intensity of 2 mA was chosen to “correct” for stimulation intensity loss when electrodes are placed further away from one another (Moliadze, Antal, & Paulus, 2010), which was done to potentially reach deeper neural structures (Dmochowski, Datta, Bikson, Su, & Parra, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, when considering trust and risk separately, the behavior of the trustor has been replicated across a large number of neuroscience studies, which indicates that the neural basis of trust lies in the activities of the prefrontal regions, striatum, amygdala, cingulate cortex, paracingulate cortex, and ventromedial prefrontal cortex (see Tzieropoulos, 2013 for a review). Transcranial direct current stimulation (tDCS) studies revealed that modulating the activity of several brain regions such as the orbitofrontal cortex, dorsolateral prefrontal cortex (DLPFC), or ventromedial prefrontal cortex may alter the participants' trustworthiness (Nihonsugi et al, 2015 ; Wang et al, 2016 ; Zheng et al, 2016 ). Moreover, numerous brain imaging studies have revealed the relationship between risk and the DLPFC.…”
Section: Introductionmentioning
confidence: 99%
“…Activating the ventromedial prefrontal cortex (vmPFC) using anodal tDCS has increased participants’ altruism and trustworthiness in economic games,17 contradicting the claim by Dubljević and Racine7 that vmPFC tDCS ‘interventions seem to promote selfish behaviour instead of moral conduct’ (p347). Anodal mPFC tDCS has reduced implicit prejudice against out-groups,18 suggesting its potential for MBE to reduce implicit racial bias.…”
Section: Prefrontal Cortex Tdcsmentioning
confidence: 99%